Adaptive impedance control of robot manipulators with parametric uncertainty for constrained path-tracking - Bonilla, Isela; Mendoza, Marco; Campos-Delgado, Daniel U.; Hernández-Alfaro, Diana E.. (Zielona Góra: Uniwersytet Zielonogórski)
The main impedance control schemes in the task space require accurate knowledge of the kinematics and dynamics of the robotic system to be controlled. In order to eliminate this dependence and preserve the structure of this kind of algorithms, this paper presents an adaptive impedance control approach to robot manipulators with kinematic and dynamic parametric uncertainty. The proposed scheme is an inverse dynamics control law that leads to the closed-loop system having a PD structure whose equilibrium point converges asymptotically to zero according to the formal stability analysis in the Lyapunov sense.
Keywords: adaptive control; constrained motion; mechanical impedance; robot manipulator